Citation Counts: Are They Good Predictors of RAE Scores? A bibliometric analysis of RAE 2001 - Surya, Mahdi; D'Este, Pablo; Neely, Andrew (Cranfield University, 2008)
The question of how best to assess research performance is clearly of great concern. In December 2007, HEFCE launched a national consultation on the future of Research Assessment, proposing that a Research Excellence Framework replaces the current Research Assessment Exercise. Fundamentally the Research Excellence Framework involves a shift to metrics. Views on the effectiveness of metrics for assessing research are mixed, so in this report we seek empirically to explore the question of whether metrics based on citation counts are strongly correlated with peer review assessments of research quality. We use data from RAE2001, covering all Departments and all Universities in the UK.